2007
DOI: 10.1111/j.1600-051x.2006.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local antimicrobial agents on excisional palatal wound healing: a clinical and histomorphometric study in rats

Abstract: Each tested antimicrobial agent when applied on an excisional wound with epithelial and connective tissue deficiency did not have a negative effect on the rate of wound closure. The best results were achieved with 1%CHX gel and Listerine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 63 publications
4
41
2
4
Order By: Relevance
“…Several study reports have been documented [7,8,9] regarding the cytotoxicity of chlorhexidine digluconate (CHX) and Listerine to human gingival fibroblasts, but these are still common chemotherapeutic agents used for postoperative care of healing oral wounds. A study performed by Kozlovsky et al [4] reported that 1% CHX gel and Listerine solution increased the rate of epithelialisation of palatal wounds in a rat model. Similarly, Bassetti and Kallenberger [29] also reported that topical application of 0.1 and 0.2% CHX resulted in undisturbed healing on day 7 following injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several study reports have been documented [7,8,9] regarding the cytotoxicity of chlorhexidine digluconate (CHX) and Listerine to human gingival fibroblasts, but these are still common chemotherapeutic agents used for postoperative care of healing oral wounds. A study performed by Kozlovsky et al [4] reported that 1% CHX gel and Listerine solution increased the rate of epithelialisation of palatal wounds in a rat model. Similarly, Bassetti and Kallenberger [29] also reported that topical application of 0.1 and 0.2% CHX resulted in undisturbed healing on day 7 following injury.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively large commensal flora and trauma from mastication impair the normal sequence of the healing process. Therefore, concern has been raised regarding the delayed healing of oral cavity wounds [4,5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effects of mouthwashes on healing process, chlorhexidine, in a concentration-and time-dependent manner, affects negatively fibroblasts and keratinocyte cell proliferation in vitro and can impair wound healing 17,32 . Kozlovsky, et al 17 (2007) demonstrated that application of 0.1% and 0.2% chlorhexidine solution on an excisional wound in rats did not have a negative effect on the rate of wound closure.…”
Section: Discussionmentioning
confidence: 99%
“…Kozlovsky, et al 17 (2007) demonstrated that application of 0.1% and 0.2% chlorhexidine solution on an excisional wound in rats did not have a negative effect on the rate of wound closure. On the other hand, C. sinensis and C. officinalis showed potent wound healing activity.…”
Section: Discussionmentioning
confidence: 99%